2013
DOI: 10.1021/ic400337m
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure, and Solution Reduction Reactions of Volatile and Thermally Stable Mid to Late First Row Transition Metal Complexes Containing Hydrazonate Ligands

Abstract: Treatment of MCl2 (M = Ni, Co, Fe, Mn, Cr) with 2 equiv of the hydrazonate salts K(tBuNNCHCtBuO), K(tBuNNCHCiPrO), or K(tBuNNCMeCMeO) afforded the complexes M(tBuNNCHCtBuO)2 (M = Ni, 65%; Co, 80%; Fe, 83%; Mn, 68%; Cr, 64%), M(tBuNNCHCiPrO)2 (M = Ni, 63%; Co, 86%; Fe, 75%), and M(tBuNNCMeCMeO)2 (M = Ni, 34%; Co, 29%; Fe, 27%). Crystal structure determinations of Co(tBuNNCHCtBuO)2, M(tBuNNCHCiPrO)2 (M = Ni, Co), and M(tBuNNCMeCMeO)2 (M = Ni, Co, Fe) revealed monomeric complexes with tetrahedral geometries about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 100 publications
0
9
0
Order By: Relevance
“…Thermal Co ALD is categorized by: (1) the introduction of the Co source precursor and co-reactant in sequential rather than simultaneous stages, with intervening purge steps to ensure that the co-reactants never cross paths in the reaction zone and that no reactions occur except on the substrate surface; and (2) Co film growth proceeding through self-limiting surface reactions that ensure precise control of film thickness and conformality with atomic level accuracy. 20,[51][52][53] These characteristics suggest the realization of excellent film conformality in extremely aggressive device topographies. The addition of plasma to one of the co-reactants (e.g., H 2 or NH 3 ) has also been shown to enhance the ALD reaction and increase film growth rates by creating a higher concentration of active co-reactant radicals.…”
Section: You Et Al (2018)mentioning
confidence: 98%
“…Thermal Co ALD is categorized by: (1) the introduction of the Co source precursor and co-reactant in sequential rather than simultaneous stages, with intervening purge steps to ensure that the co-reactants never cross paths in the reaction zone and that no reactions occur except on the substrate surface; and (2) Co film growth proceeding through self-limiting surface reactions that ensure precise control of film thickness and conformality with atomic level accuracy. 20,[51][52][53] These characteristics suggest the realization of excellent film conformality in extremely aggressive device topographies. The addition of plasma to one of the co-reactants (e.g., H 2 or NH 3 ) has also been shown to enhance the ALD reaction and increase film growth rates by creating a higher concentration of active co-reactant radicals.…”
Section: You Et Al (2018)mentioning
confidence: 98%
“…In support of this proposal, we previously observed that growth of cobalt metal only occurred upon pretreatment of the ruthenium substrate with 50 cycles of a pulse sequence comprising Co((Me) (iPr)COCNtBu) 2 (20.0 s)/N 2 purge (5.0 s)/BH 3 (NHMe 2 ) (1.0 s)/N 2 purge (10.0 s). 35 To probe the importance of precursor 1, we carried out depositions at 175, 200, and 225 °C on ruthenium, platinum, silicon(100), and silicon dioxide substrates using the alternative cobalt precursor 3 42 and formic acid with a pulse sequence of 3 (3.0 s)/N 2 purge (10.0 s)/formic acid (0.2 s)/N 2 purge (10.0 s) with 1000 cycles. No film growth was observed.…”
mentioning
confidence: 99%
“…The lack of film growth using 3 could arise from its higher thermal stability compared to 1 (dec 1, 235 °C; 37 3, 260 °C42 ) and the fact that thermal decomposition of 3 does not afford cobalt metal. 42 On the basis of the cobalt metal ALD growth, we attempted an analogous nickel metal film growth process employing bis(1,4-di-tert-butyl-1,3-diazabutadienyl)nickel(II) (4) 37 and formic acid at 180 °C using a pulse sequence of 4 (5.0 s)/N 2 purge (10.0 s)/formic acid (0.2 s)/N 2 purge (10.0 s) on ruthenium substrates with 1000 cycles. No films were observed by SEM.…”
mentioning
confidence: 99%
“…In complexes 3 – 7 , as shown in Figures 2–6, the Co–O bond lengths between the central cobalt ion and the oxygen of the β-diketonate ligands were 2.0017(12), 2.015(3), 2.0187(15), 2.0048(11), and 1.996(7) Å, respectively, which were again shorter than that for similar β-diketonate complexes of cobalt (2.064(4) Å for [Co(acac) 2 (TMEDA)], 2.046(3) Å for [Co(acac) 2 (DMAPH)] 2 , 23 2.034(3) Å for [Co(acac) 2 (py) 2 ], and 2.036(12) Å for [Co(tmhd) 2 (py) 2 ]). 24 However, the Co–O bond lengths for complexes 3 – 7 are longer than those in the Co(thd) 3 complex (1.869(2) Å) 25 and in [Co( t BuNNCHCRO) 2 (R = t Bu, i Pr, Me)] 26 (average Co–O bond length is 1.915(1) Å). An increase in the Co1–O1–Co1 i bond angle and relative increase in the Co···Co distances were observed between complex 1 and complexes 3 – 7 (Table 2).…”
Section: Resultsmentioning
confidence: 95%